Interfacial bonding in metal-matrix composites reinforced with metal-coated diamonds - Margaritis, Dimitris-Peter (2003)
Diamond reinforced metal-matrix composites (MMCs) are utilised for cutting, drilling, grinding and polishing a variety of materials, in many cases being the most efficient and economic choice. The increased cost of synthetic diamond abrasives has led to constant search for ways to extent diamond tool life. This has been realised by introducing chemical reactions at the interfaces in order to develop chemical bridges between diamonds and metals that prolong the retention of crystals at the operating surfaces of the tools. Alloying the matrix with carbide forming metals is a way to introduce interfacial reactivity, but involves problems with concentrating the alloying element at the interfacial region and may cause alteration of the wear resistance characteristics of the binder, which may be an undesirable effect. A recent development and alternative method to alloying is the coating of the diamonds with carbide forming metals, offering unique advantages. Although metal-coated diamonds are commercially available, the effectiveness of their usage and the understanding of interfacial phenomena occurring in composites reinforced with such abrasives still remain unexplored. The work carried out in this research has examined the interfacial bonding in diamond MMCs reinforced with metal-coated crystals.